Efeitos da temperatura e do estado metabólico sobre a função cardíaca do jacaré-de-papo-amarelo (Caiman latirostris) - Lopes, André Guelli (Universidade Federal de São Carlos, 2014)
Phenomena as feeding and thermoregulation can challenge both the cardiac output and heart rate (fH). Postprandial changes in many physiological patterns are typically recorded for ectotherms, although predominantly studied in snakes. Furthermore, thermoregulation is a critical process to ensure different survival and reproduction strategies from reptiles. Ventricular preparations in vitro were used to investigate the inotropic plasticity at 30 ºC and 25 ºC and during fasting (30 days fasting group) and after feeding (2 days digesting group). No significant differences were verified in the relative ventricular mass (RVM) after feeding. The peak tension (Fc) was significantly higher and rates (dFc/dt) of contraction (TC) and relaxation (TR) were faster at 25° C than at 30° C for both experimental groups. However, feeding caused significant increase in peak tension (PT) at both temperatures (396.7 % at 30 ºC and 416.7 % at 25 ºC). A significant post-rest potentiation was recorded for digesting group at 25 ºC (121.0 ± 6.4 %), which was inhibited by ryanodine (86.0 ± 2.9 %). At 30 ºC, myocytes from fasting group were able to support higher frequencies (up to 1.6 Hz) than at 25 ºC (up to 1.0 Hz), even with the sarcoplasmic reticulum (SR) blocked by 10 μM ryanodine (RYA). Data from digestion group showed greater values of the Fc and reached higher frequencies than fasting group, at both temperatures. However, pre-treatment with RYA decreased PT in frequencies between 1.4 and 1.8 Hz for digesting group at 30 ºC. Sarcolemma mechanisms were more representative in the fasting group at 25 ºC, but the SR must contribute to increased speed of contractility under those conditions. During SDA, the SR seem representative at 25 ºC, however the positive inotropic effect caused by SDA enlarged sarcolemma mechanisms representativeness. The SR significance at 30 °C seems critical during high frequencies. At this temperature, the SDA increases the contractility efficiency, even with the RS blocked, despite the relaxation and Fc development at high frequencies been present impaired. Our results indicate that Caiman latirostris myocytes show large inotropic plasticity at different temperatures, frequencies and metabolic states.
Keywords: Coração; Caiman latirostris; Contratilidade; Temperatura; Ação dinâmica específica; Retículo sarcoplasmático; Caiman latirostris; Sarcoplasmic Reticulum; Peak Tension; Specific dynamic action-SDA; Temperature; CIENCIAS BIOLOGICAS::FISIOLOGIA